The Examination of the Effects of Quercus Aegilops Extract Used as Natural Mordant on Colourfulness Features of Natural Dyeing - (:unkn) unknown (IEEE, 2016)
Ecological textiles or eco textiles means a recyclable product or a product that can be recycled into an environmentally harmless product which has been produced by paying regard to environment during all process steps from, which does not harm the user. Natural dyeing, which is of great importance in the textiles industry in terms of being economical and applicable, has a number of advantages thanks to its features such as health, ecological cycle and providing biological availability. With the use of natural mordant as a binder during dyeing both dyeing and mordant become important for environmentally friendly processes. This study examines the usability of natural dye extract obtained from Helichrysum Arenarium, which has a wide range around the world, and Quercus Aegilops natural mordant in dyeing of Karabuk Eflani cloth, a regional weaving. Eflani cloth is made from 100% cotton staple. In this study Eflani cloth woven from 100% cotton yarn with Helichrysum Arenarium was dyed with 5 different concentrations of natural mordant. L*a*b* values of the samples of dyed cotton cloth were measured and compared using CIE L*a*b* colour space system. Also, lightfastness and washing features of dyeing were examined. Colour scale was darker and more vivid in dyeing made with Quercus Aegilops natural mordant compared to dyeing made without mordant.
Keywords: eflani cloth; helichrysum arenarium; natural dyeing; natural mordants; quercus aegilops; GALLNUT; COTTON; TEXTILES; WOOL; SILK; DYES